New campus-Memorial Fountain-0008 (1964)
The Fresno State College Memorial Court Fountain serves as a living memorial to some 100 college students who lost their lives during World War II and the Koream crisis. The college, now more than 50 years old and a member of the California Sate College System, currently has 6,500 students enrolled in the liberal arts and professional programs.